I found God in me: a womanist biblical hermeneutics reader - Smith, Mitzi J. (Wipf and Stock Publishers, 2015)
I Found God in Me is the first womanist biblical hermeneutics reader. In it readers have access, in one volume, to articles on womanist interpretative theories and theology as well as cutting-edge womanist readings of biblical texts by womanist biblical scholars. This book is an excellent resource for women of color, pastors, and seminarians interested in relevant readings of the biblical text, as well as scholars and teachers teaching courses in womanist biblical hermeneutics, feminist interpretation, African American hermeneutics, and biblical courses that value diversity and dialogue as cru